1995
DOI: 10.1523/jneurosci.15-05-03231.1995
|View full text |Cite
|
Sign up to set email alerts
|

A novel, abundant sodium channel expressed in neurons and glia

Abstract: A novel, voltage-gated sodium channel cDNA, designated NaCh6, has been isolated from the rat central and peripheral nervous systems. RNase protection assays showed that NaCh6 is highly expressed in the brain, and NaCh6 mRNA is as abundant or more abundant than the mRNAs for previously identified rat brain sodium channels. In situ hybridization demonstrated that a wide variety of neurons express NaCh6, including motor neurons in the brainstem and spinal cord, cerebellar granule cells, and pyramidal and granule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
162
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(173 citation statements)
references
References 45 publications
11
162
0
Order By: Relevance
“…In the adult, both zebrafish genes are predominantly expressed in neural tissue (brain, spinal cord and eye), similar to the expression pattern of SCN8A in mammals (Krzemien et al 2000;Schaller et al 1995;Tzoumaka et al 2000). Interestingly our RT-PCR analyses also reveal expression in skeletal and cardiac muscle, as recently reported for mammalian SCN8A in cardiac tissue (Dhar Malhotra et al 2001;Maier et al 2002).…”
Section: Scna Gene Expression In Teleosts and Mammalssupporting
confidence: 87%
“…In the adult, both zebrafish genes are predominantly expressed in neural tissue (brain, spinal cord and eye), similar to the expression pattern of SCN8A in mammals (Krzemien et al 2000;Schaller et al 1995;Tzoumaka et al 2000). Interestingly our RT-PCR analyses also reveal expression in skeletal and cardiac muscle, as recently reported for mammalian SCN8A in cardiac tissue (Dhar Malhotra et al 2001;Maier et al 2002).…”
Section: Scna Gene Expression In Teleosts and Mammalssupporting
confidence: 87%
“…SCN8A is expressed broadly throughout the central and peripheral nervous systems during early embryogenesis (Schaller et al, 1995;Krzemien et al, 2000;Schaller and Caldwell, 2000). Previous work has shown that zebrafish scn8aa mRNA expression begins early (16 hpf) and occurs in many regions of both the central and peripheral nervous systems (Tsai et al, 2001).…”
Section: Scn8aa and Scn8ab Gene Expressionmentioning
confidence: 99%
“…Na v 1.6 (also termed SCN8A or PN4) is a sodium channel that is expressed throughout the CNS and the PNS (Burgess et al, 1995;Schaller et al, 1995) and is abundant at the axon initial segment, at the nodes of Ranvier Krzemien et al, 2000;Tzoumaka et al, 2000;Boiko et al, 2001), and along nonmyelinated axons of the PNS . Na v 1.6 produces a fast inactivating, TTX-sensitive (TTX-S) sodium current (Dietrich et al, 1998;Smith et al, 1998;Herzog et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%